Addressing The Human Rights Impacts Of Economic Globalisation: An Analysis From Soft Law and Islamic Perspectives - Nisar Mohammad Ahmad; Irwan Mohd Subri; Ahmad Wifaq Mokhtar; Nisar Mohammad Ahmad; Halyani Hassan (2024)
The conference was held on Nov 29th-30th, 2014 at Flamingo Hotel, Penang